The Use of Re-entry Devices in Aortoiliac Occlusive Disease - Pescatori, Lorenzo C.; Tacher, Vania; Kobeiter, Hicham (Frontiers in Cardiovascular Medicine, 2020)
Endovascular approach is thefirst choice treatment in patients suffering from aortoiliac occlusions. Nevertheless, standard endoluminal revascularisation fails in treating occlusions in about 20% [1] of cases. Thus, subintimal revascularisation can be a solution, but it fails in 25% [2] of cases as well. In the last decades, different devices have been created, in order to ease the cross back into the true lumen, when standard subintimal revascularisation does not work or risks to occlude important collateral vessels. Herein, we revise the currently available re-entry devices and their application in the aortoiliac occlusive pathology.